Effectiveness of Equine-Assisted Activities and Therapies for Children with Autism Spectrum Disorder: An Update - Leonardo Zoccante; Sara Sabaini; Sophia Marlene Bonatti; Erika Rigotti; Camilla Lintas; Michele Marconi; Marco Zaffanello (Children)
Background/Objectives: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition requiring personalised therapeutic approaches. This study evaluated the effectiveness of Equine-Assisted Activities and Therapies (EAATs) in 86 children with varying ASD severity levels (levels 1–3). Methods: Vineland Adaptive Behaviour Scales and the Parenting Stress Index were used. Between May 2022 and October 2023, participants completed 20 weekly sessions of 45 min each, tailored to their individual needs. Results: Children with level 3 ASD demonstrated greater challenges in communication (level 1: 67.1 ± 29.0 vs. level 3: 30.0 ± 12.6; p < 0.001), daily living skills (81.0 ± 26.8 vs. 42.6 ± 18.1; p < 0.001), and socialisation (72.2 ± 23.2 vs. 37.3 ± 14.2; p < 0.001). Parental distress was higher in cases of greater ASD severity. Nevertheless, significant improvements were observed across the entire cohort in daily living skills (58.3 ± 25.5 vs. 67.8 ± 29.0; p = 0.023), with particularly notable outcomes in children with level 1 ASD (65.7 ± 26.9 vs. 81.0 ± 26.8; p = 0.010). While increases in socialisation were noted among children with level 1 ASD, these were not statistically significant (p = 0.073). Conclusions: EAAT fosters improvements in daily living skills, particularly in children with level 1 ASD, and has a positive impact on socialisation. For children with more severe ASD, targeted interventions are required.